Level of adolescent behavior towards noise-induced hearing loss - Wulan Suci Lestari; Indra Zachreini (Institute of Computer Science (IOCS), 2026)
Noise-induced hearing loss (NIHL) is a permanent health problem caused by continuous exposure to high-intensity sounds. In Indonesia, the prevalence of noise-induced hearing loss is 4.6%, one of the highest in Southeast Asia. NIHL can be prevented, but many adolescents still do not have appropriate preventive behaviors. This study aims to determine the relationships among adolescents' knowledge, attitudes, and actions regarding NIHL prevention in Aceh Province. The study used a cross-sectional analytical design with a sample of 143 adolescents aged 10–24 years, selected by consecutive sampling. The analysis results showed that the majority of respondents had good knowledge (78.8%) and good attitudes (86.1%). Still, there was no significant relationship between knowledge and actions (p = 0.361), attitudes and actions (p = 0.204), or knowledge and attitudes (p = 0.726). These findings indicate that good knowledge and attitudes do not necessarily promote effective preventive actions. Therefore, a more appropriate intervention approach is needed to encourage behavioral change among adolescents in preventing noise-induced hearing loss.